If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 4) + 3(x + -1) = -15 Reorder the terms: 4(4 + x) + 3(x + -1) = -15 (4 * 4 + x * 4) + 3(x + -1) = -15 (16 + 4x) + 3(x + -1) = -15 Reorder the terms: 16 + 4x + 3(-1 + x) = -15 16 + 4x + (-1 * 3 + x * 3) = -15 16 + 4x + (-3 + 3x) = -15 Reorder the terms: 16 + -3 + 4x + 3x = -15 Combine like terms: 16 + -3 = 13 13 + 4x + 3x = -15 Combine like terms: 4x + 3x = 7x 13 + 7x = -15 Solving 13 + 7x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 7x = -15 + -13 Combine like terms: 13 + -13 = 0 0 + 7x = -15 + -13 7x = -15 + -13 Combine like terms: -15 + -13 = -28 7x = -28 Divide each side by '7'. x = -4 Simplifying x = -4
| 3(2g+1)-2(g+5)= | | 27x+17=-30 | | eEx=36 | | 15x+21=7x-19 | | x^3+4= | | 64x=24 | | 25x^2+165x+200=0 | | 40a^2+195a+140=0 | | 135-v=223 | | 11e-4e= | | 6x+10=-56-5x | | 226=-y+163 | | 6x+50=13x-8 | | fx=-2/7×2 | | 6+n=6n | | 84=-u+270 | | 3n^2+24n+21=0 | | fx=-2/7x | | y=1/2(6)+2 | | -2x+4=-6+4 | | 3x-8=6x-14 | | -16x+12x+7x+5=-9 | | 2x^4+9x^3-10x^2= | | 3x-6=10x-8 | | 5m^2-245=0 | | 6(4b+5)=78 | | 7(3x-5)=8 | | 3x-24=5x-32 | | -1-3/8n=5-6 | | f(x)=-2x^2-17x+30 | | 5b^2+25b+30=0 | | 3(x-4)+2(3x-1)=-3(-3x+1)+2 |